Reporting of Participants' Sex, Race, Ethnicity, and Socioeconomic Status in Pituitary Surgery Literature - Nourmahnad, Anahita; Purrinos, Julian A.; Grozovsky, Renata; Richardson, Angela M.; Levine, Corinna G. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Social determinants of health (SDOH) are associated with differential outcomes after pituitary tumor treatment. However, the specific impact of SDOH is not well characterized. One reason may be the lack of collection and reporting of sociodemographic variables in the literature. This study aims to evaluate the frequency of reporting and distribution of participants' sex, race, ethnicity, income, and education level within pituitary surgery literature. We will compare the reported clinical research population demographics to the 2020 U.S. census.Methods A systematic review was performed by searching PubMed, Cochrane, and Embase databases for pituitary surgery clinical research published between July 1, 2021 to June 30, 2022. We excluded studies that lacked a comparison group, were not original research (i.e., systematic reviews, meta-analysis), or included national databases and registry data.Results The final analysis included 92 studies. A total of 99% of studies collected data on subject sex. On average 49% (range: 14–100%) of study populations were male. Only 4% (n = 4) studies included racial demographic data. Two studies included information on participants' ethnicity and two included education background. No studies included income or insurance data. Four U.S. studies included demographic distribution, and the reported race and ethnicity percentages are similar to the U.S. 2020 census distribution.Conclusion Most clinical pituitary research collects and reports data on participant sex. However, very few studies collect and report data on other sociodemographic variables that can play a role in outcomes. The lack of sociodemographic information in clinical research literature makes it difficult to determine the role of SDOH on pituitary surgery outcomes.
Keywords: pituitary surgery; health disparities; social determinants of health; sociodemographics